Information and Communication Technologies in Postgraduate Training of Primary Care Doctors: A New Look at the Problem of Using Online Resources During the COVID-19 Pandemic - Tsodikova, Olga; Korzh, Oleksii; Hyria, Maryna (Technium Social Sciences Journal, 2020)
The experience of using information and communication technologies of distance learning in the process of postgraduate education of primary care physicians is considered. The implementation of various online resources in the training of health professionals in quarantine activities related to the COVID-19 pandemic, highlights the problem of information literacy and the use of information technology among physicians of all ages and psychotypes, and shows that the latest resources of telecommunications and computers. computer technologies should be widely implemented in all areas of health care.